The Parallel Process - Dramatherapy sessions with an older non-verbal client. Issue 3 (December 2019) - Sweet, Rosie
An article outlining a case study examining a parallel process travelled by a dramatherapist and stroke victim. With all therapeutic relationships we embark on a journey with our client. This article examines just such a journey, one where the therapist and client moved together in a parallel process. These dramatherapy sessions were conducted with an older, non-verbal stroke victim and examine how the therapist experienced the transference changing through the therapy. This article explores work with a non-verbal individual with limited motor ability and how as dramatherapists we communicate with these individuals to create a therapeutic relationship and therefore meaningful therapeutic work.